Preventive Effects of Nicorandil Against Contrast-Induced Nephropathy in Patients With Moderate Renal Insufficiency Undergoing Percutaneous Coronary Intervention. (February 2020) - Zhang, Peng; Li, Wen-yuan; Yang, Shi-Cheng; Fu, Nai-Kuan; Liu, Xiao-Gang; Zhang, Xue; Cong, Hong-Liang; Lin, Wen-Hua; Tian, Feng-Shi; Lu, Cheng-Zhi; Zhang, Jing
We investigated the preventive effect of nicorandil on contrast-induced nephropathy (CIN) in patients with moderate renal insufficiency undergoing percutaneous coronary intervention (PCI). A total of 250 patients with a creatinine clearance (crCl) ≤60 mL/min undergoing PCI were randomly assigned to either a nicorandil group (nicorandil 10 mg 3 times/d and hydration; n = 125) or a control group (hydration only; n = 125). The first end point was the incidence of CIN defined as an increase in serum creatinine (Scr) levels by ≥0.5 mg/dL or ≥25% within 72 hours after exposure to the contrast medium. The secondary end points were (1) changes in Scr, blood urea nitrogen, and crCl and (2) the incidence of major adverse events during hospitalization. The incidence of CIN was 1.6% (2/125) in the nicorandil group and 9.6% (12/125) in the control group ( P = .011). There was no obvious difference in the incidence of major adverse events during hospitalization between the nicorandil and the control group (4.0% vs 4.8%, P = 1.000). Multivariate logistic regression analysis showed that nicorandil was a protective factor for CIN (odds ratios = 0.126, 95% confidence interval: −19.996 to −0.932, P = .012). Prophylactic administration of nicorandil may prevent against CIN in patients with moderate renal insufficiency undergoing PCI.